Al-TAJDID FI ‘ILM AL-KALAM: NAZARIYYAT NAQDIYYAH - Musab Alkhair Idris (Indonesian Journal of Islamic Literature and Muslim Society, 2017)
This article aims to describe the nature and function of Islamic theology, the call for modernization in this field, as well as some theories and standards in its modernization. The study found that a contemporary Islamic theologian, as long as he was aware of the nature and function of theology, mastered the field of theology that his predecessors had presented, following developments in the field of thought and philosophy, including the methods of   da'wah in “the new religion” as a theological phenomenon, he will produce a new theology with all its beliefs and credo, that can be compared with other beliefs. Considering that the general approach in the study of theology is deductive-argumentative, the researcher of this field can be used the other approaches, such as historical approaches, comparative, critical philosophy, as well as structural analyzes toward the theological references, that are rooted either from new or old references.